Morphological, Physiological and Biochemical Response to Low Temperature Stress in Tomato (Solanum lycopersicum L.): A Review - Yadav, D. K.; Meena, Yogendra K.; Bairwa, L. N.; Singh, Uadal; Bairwa, S. K.; Choudhary, M. R.; Singh, A. (International Journal of Bio-resource and Stress Management, 2021)
Growth and productivity are traumatized by the low temperature that triggers a series of physiological, morphological, molecular and biochemical changes in plants that eventually disturb plant life. Most of the cultivable lands of the world are adversely affected by temperature stress conditions which have an adverse impact on global tomato productivity. Plants undergo several water related metabolic activities for their survival during cold stress conditions. Understanding the morphological, physiological and biochemical reactions to low temperature is essential for a comprehensive view of the perception of tomato plant tolerant mechanism. This review reports some aspects of low temperature inflated changes in physiological and biochemical in the tomato plant. Low temperature stress influences the reproductive phases of plants with delayed flowering which enhance pollen sterility resultant drastically affects the harvest yield. It also decreases the capacity and efficiency of photosynthesis through changes in gas exchange, pigment content, chloroplast development and decline in chlorophyll fluorescence photosynthetic attributes. Amassing of osmoprotectant is another adaptive mechanism in plants exposed to low temperatures stress, as essential metabolites directly participate in the osmotic adjustment. Furthermore, low temperature stress enhanced the production of reactive oxygen species (ROS) which may oxidize lipids, proteins and nucleic acids which bring in distortion at the level of the cell. At the point when extreme reactive oxygen species produced, plants synthesize antioxidant enzymes and osmoprotectants that quench the abundance of reactive oxygen species. These reviews focus on the capacity and techniques of the tomato plant to react low temperature stress.